Strength and stability criteria for thin-walled stainless steel circular hollow section members under bending - Kıymaz, Güven (ELSEVIER SCI LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND, 2005)
A series of tests consisting of various cross-section geometries were performed on structural stainless steel circular hollow sections (CHS) subjected to bending. The test program comprised a total of eight tests on CHS in two grades of stainless steel, namely 304 and Duplex 2205. For each grade four sections, each with a different slenderness, were tested, in order to cover a range of structural responses. Measurements of overall geometric imperfections and material properties were conducted. The test strengths are compared with the strengths predicted using the American, Australian and European specifications for cold-formed stainless steel structures. In the light of the test results and code recommendations, strength and cross-section classification criteria for stainless steel circular hollow section members in bending are examined. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: stainless steel; circular hollow sections; bending resistance; slenderness limit; paslanmaz çelik; dairesel profiller; eğilme dayanımı; narinlik sınırı